Knowledge, attitudes, and practices of mothers towards childhood Immunizations at Young Child Clinics of Mildmay Uganda Hospital, Wakiso District. A cross-sectional study. - Acac, Stanley; Nansereko, Hasifa; Nalubega, Jane Frank; Akankwasa, Edith (Student’s Journal of Health Research Africa, 2025)
Background. Globally, it is estimated that around 22.6 million infants were partially protected by immunization services. In Uganda, only 52 percent of children aged 12-23 months were fully vaccinated. This assessed the knowledge, attitudes, and practices on immunization among mothers attending the young child clinic at Mildmay Uganda hospital. Methods. A descriptive cross-sectional study design was employed, using quantitative data collection methods. Over five days, 30 mothers were selected through simple random sampling. Data were gathered using a structured, closed-ended questionnaire and analyzed manually, with results entered into Microsoft Excel (2013) and presented using tables, pie charts, and graphs. Results. Most of the participants were aged 25-29(40%) and had secondary education (50%), and 100,000-300,000 Ugandan shillings monthly (47%). All mothers were aware of childhood immunization,70% citing disease prevention as its purpose, and all knew the first dose is given at birth. However, 53% were unaware of the required routine visits. Most received information through radio or TV (60%), while 80% believe in the benefits of vaccination,60% felt unsafe vaccinating their children, and 70% opposed compulsory vaccination. Additionally, 53% didn’t advise others to vaccinate. Regarding practices, many missed vaccine schedules (63%), skipped vaccines (67%) or didn’t complete them (53%), and 87% used pain relievers post-vaccination Conclusion. Mothers had general awareness of childhood immunization, but gaps in knowledge, negative attitudes, and poor practices hindered full adherence to vaccination schedules. Recommendation. There is a need for targeted health education and community outreach to improve mothers’ knowledge, attitudes, and practices toward childhood immunization.